Students’ Participation and Collaboration Skills through RADEC Learning Model and the Influencing Factors - Hanum, Citra Bahadur; Sopandi, Wahyu; Sujana, Atep (Mimbar Sekolah Dasar, 2023)
This study aims at identifying forms of participation and collaboration through RADEC learning and the influencing factors. The subject of this study comprised 32 students (18 males and 14 females) attending an elementary school in Bandung city. Case study with a qualitative approach was employed as the method of the study by utilizing instruments such as observation sheets, student work sheet, and field notes. Obtained data were analyzed using Miles Huberman's (1992) technique with data validation using reference material techniques and methodological triangulation. The results reveal that (1) doing assignments, asking questions, delivering opinions and arguments, giving responses and making conclusion are forms of participation students engage in the classroom, (2) students collaborated through group work, active participation and contribution in the group assignment, listening and discussing  a variety of topics, showing appreciation, matching assignments and work, cooperate to gain ideas and realize them through a respectful and proper decision making, and (3) several factors influence the students’ participation and collaboration, namely confidence, hard work, and teachers’ stimulation. These results signify that RADEC learning is able to stimulate students’ participation and collaboration.